Pengaruh Social Media Marketing Dan Celebrity Endorser Terhadap Purchase Intention Dengan Brand Awareness Sebagai Variabel Intervening - Sultan Hasan Nudin; R.A. Nurlinda (Pusat Riset dan Inovasi Nasional, 2023)
The research objective was to determine the direct effect of social media marketing and celebrity endorsers on purchase intention, then to determine the direct effect of social media marketing, celebrity endorsers, brand awareness on purchase intention and the final objective is to determine the indirect effect of social media marketing, celebrity endorsers on purchase intention through brand awareness. Data collection was carried out through a survey with a questionnaire. Distribution of questionnaires using the Google form via social media. The population in this study are all people who know Erigo products. Questionnaires collected as many as 160 respondents. The sampling technique is non-probability with a purposive sampling procedure. In this study using a quantitative approach. The results of the research analysis, namely social media marketing, celebrity endorsers have a positive effect on purchase intention. social media marketing, celebrity endorser, brand awareness has a positive effect on purchase intention. Social media marketing has a positive effect on purchase intention through brand awareness and celebrity endorsers have a positive effect on purchase intention through brand awareness. The results of the study are expected to provide input to everyone to find out about social media marketing and celebrity endorsers which can increase product brand awareness and raise the intention to buy Erigo products.